Ferroptosis in the tumor microenvironment: perspectives for immunotherapy. Issue 9 (September 2021) - Xu, Huanji; Ye, Di; Ren, Meiling; Zhang, Hongying; Bi, Feng
Abstract : Targeting ferroptosis, which provokes lipid peroxidation in cancer cells, presents potentially new avenues for anticancer therapy. Recent studies have begun to explore how immune cells in the tumor microenvironment (TME) respond and adapt to lethal lipid peroxides (LPOs). A better understanding of this process in the TME is likely to uncover another side of ferroptosis in cancer immunity and promote the development of ferroptosis-targeted therapy. This Opinion article overviews the main metabolic processes in ferroptosis, summarizes the emerging roles of ferroptosis not only in immune cells in the TME but also in the crosstalk between tumor cells and immune cells, and presents a perspective on the targeting of ferroptosis in cancer immunotherapy. Highlights: Different immune cells in the TME display distinct sensitivities to ferroptosis. Ferroptosis is a metabolic vulnerability of activated CD8 + T cells, while inhibition of ferroptosis can promote the survival and antitumor effects of CD8 + T cells in tumors. In tumors with different immunophenotypes, ferroptosis inducers might have distinct impacts on cancer immunity, which may determine the efficacy of immune checkpoint inhibitor immunotherapy.